Faktor-Faktor Yang Mempengaruhi Kecemasan Pada Ibu Hamil Trimester III : Scoping Riview - Anisa Rivainy Marudju; Meyliana Dinny Tulandi; Dwyfa Hapili; Jenifer Darenoh; Nurhaya Hamajen; Fathia Nur Mawaddah Uno; Atik Sunarmi (Jurnal Medika Nusantara, 2024)
Background: Anxiety is a psychological disorder that commonly occurs during pregnancy. The third trimester of pregnancy (TM III) is a time of active preparation for the birth of a baby and a change in the role of being a parent, such as focusing attention on the presence of the baby, most pregnant women are in a state of anxiety, the underlying thing is that the mother feels worried about the birth process that she will face. The Scoping Review was carried out with the aim of mapping existing evidence regarding the factors that influence anxiety in pregnant women. The databases used are Pubmed and Google Scholar with inclusion criteria in the form of original articles, published in 2019-2024, published in Indonesian, articles discussing what factors can influence anxiety in pregnant women, free full text articles and open access.